Danuty Abrahamowicz szkoła przekładu - Buczek, Marta (Przekłady Literatur Słowiańskich, 2016)
Danuta Abrahamowicz’s school of translation The author of the article focuses on the specific school of translation formulated by the well‑known Polish translator of Slovak literature, Danuta Abrahamowicz in the Slovak environment of the second half of the 20th century. The article defines all aspects of Abrahamowicz’s translatological activities. Her literary studies, critical, publishing, editorial and translation activity are examined in the article and finally, the article shows the ways in which Abrahamowicz perceived translation and the various ways of implementing it in a new horizon of reception to become a fact of the target culture. Key words: translation, Slovak literature in Polish translation, Danuta Abrahamowicz, Polish literature in Slovakia, Polish and Slovak literary contacts